How managerial coaching promotes employees' affective commitment and individual performance - Ribeiro, N. (2020)
Abstract Purpose: This study sought to provide a more comprehensive understanding of how managers’ coaching skills can affect individual performance through the mediating role of affective commitment. Design/methodology/approach: The sample included 198 employees from diverse organizations. Based on an online survey, respondents assessed their managers’ coaching skills and reported their own individual performance and affective commitment to their organization. Findings: The findings show that managers’ coaching skills have a positive impact on individual performance and affective commitment, with the latter mediating the relationship between the first two variables. Research limitations/implications: Additional studies with larger samples are needed to understand more fully not only the impact of managers’ coaching skills on individual performance but also other psychosocial variables affecting that relationship. Practical implications: Organizations can increase employees’ affective commitment and individual performance by encouraging managers to integrate more coaching skills into their leadership styles. Originality/value: This study is the first to integrate managers’ coaching skills, affective commitment, and individual performance into a single research model, thereby extending previous research on this topic.